Taking a Stand: Exploring the Role of the Scientists prior to the First Pugwash Conference on Science and World Affairs, 1957 - Nickerson, Sylvia (Scientia Canadensis, 2013)
In 1957, a small group of world-renown scientists gathered in Pugwash, Nova Scotia to discuss the growing threat of nuclear arms. Funded by industrialist Cyrus Eaton and spearheaded by philosopher Bertrand Russell and physicist Joseph Rotblat, this 1957 meeting founded an organization of scientists that believed they had a duty to speak out against escalating nuclear testing and what they saw as the irresponsible use of science. However, not every scientist felt that it was appropriate to take a public and political stand. This paper gives a brief history of the Pugwash movement and how its first meeting came to be held in Pugwash, Nova Scotia. The perspectives of involved scientists are examined, contrasting the attitudes of participants in the conference with the attitudes of scientists who declined a public role. This paper explores how scientists perceived their own responsibility to act, examining the willingness to use their cultural identity as scientists to lobby for a particular political position.